ENSO and IOD teleconnections for African ecosystems: evidence of destructive interference between climate oscillations - C. A. Williams; N. P. Hanan (Biogeosciences, 2011)
Rainfall and vegetation across Africa are known to resonate with the coupled ocean-atmosphere phenomena of El Niño Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD). However, the regional-scale implications of sea surface temperature variability for Africa's photosyntheis have received little focused attention, particularly in the case of IOD. Furthermore, studies exploring the interactive effects of ENSO and IOD when coincident are lacking. This analysis uses remotely sensed vegetation change plus a land surface model driven with observed meteorology to investigate how rainfall, vegetation, and photosynthesis across Africa respond to these climate oscillations. In addition to the relatively well-known ENSO forcing, the IOD induces large departures of photosynthesis across much of Africa associated with anomalies in rainfall and vegetation greenness. More importantly, sizeable independent effects can be suppressed or even reversed by destructive interferences during periods of simultaneous ENSO and IOD activity. For example, effects of positive IOD on southeastern Africa tended to dominate those of El Niño during their coincidence spanning 1997–1998, with sign reversal of El Niño's typically strong suppression of photosynthesis in this region. These findings call into question past analyses examining teleconnections to ENSO or IOD in isolation, and indicate the need to consider their simultaneous states when examining influences on hydroclimatic and ecological conditions across Africa.